(untitled) - Elliott, Alan C. (New York, 2000)
In this complete guide, expert Alan Elliott saves you the time and expense of learning the ins and outs of Internet auctions the hard way. He reviews all the best auction sites and, step-by-step, teaches you everything you need to know to safely and successfully participate both as a buyer and a seller
Keywords: Internet auctions,Internet,Đấu giá qua mạng internet